Performance Evaluation of Real-Time RT-PCR Assays for the Detection of Severe Acute Respiratory Syndrome Coronavirus-2 Developed by the National Institute of Infectious Diseases, Japan - Shirato, Kazuya; Tomita, Yuriko; Katoh, Hiroshi; Yamada, Souichi; Fukushi, Shuetsu; Matsuyama, Shutoku; Takeda, Makoto (Japanese Journal of Infectious Diseases, 2021)
Soon after the 2019 outbreak of coronavirus disease 2019 in Wuhan, China, a protocol for real-time RT-PCR assay detection of severe acute respiratory syndrome coronavirus (SARS-CoV-2) was established by the National Institute of Infectious Diseases (NIID) in Japan. The protocol used Charité’s nucleocapsid (Sarbeco-N) and NIID nucleocapsid (NIID-N2) assays. During the following months, SARS-CoV-2 spread and caused a global pandemic, and various SARS-CoV-2 sequences were registered in public databases, such as the Global Initiative on Sharing All Influenza Data (GISAID). In this study, we evaluated the S2 assay (NIID-S2) that was newly developed to replace the Sarbeco-N assay and the performance of the NIID-N2 and NIID-S2 assays, referring to mismatches in the primer/probe targeted region. We found that the analytical sensitivity and specificity of the NIID-S2 set were comparable to those of the NIID-N2 assay, and the detection rate for clinical specimens was identical to that of the NIID-N2 assay. Furthermore, among the available sequences (approximately 192,000), the NIID-N2 and NIID-S2 sets had 2.6% and 1.2% mismatched sequences, respectively, although most of these mismatches did not affect the amplification efficiency, except the 3′ end of the NIID-N2 forward primer. These findings indicate that the previously developed NIID-N2 assay is suitable for the detection of SARS-CoV-2 with support from the newly developed NIID-S2 set.